L’Horloge des siècles (1902) d’Albert Robida No future ou la vie à rebours - Lévêque, Laure (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
French writer Albert Robida, renowned for his futuristic works of fiction writtenin a bitter-sweet tone, somehow broke away from his usual inspiration in The Clock of theCenturies (published in 1902), as electric life short-circuited. This atypical novel opens up,in the early stages of the twentieth century Robida now refuses to anticipate and explore,with a cataclysm that all but extinguishes every form of life on earth and gives a symbolicwarning that there is something wrong in the civilized world. Survival is organized, but Robidathen subverts the “post-apocalyptic” narrative to introduce an unprecedented variation: thesurvivors realize that, after the catastrophe, an “out-of-joint” universe, in which the hands oftime are now ticking in reverse, has now taken over. Comic relief is provided by the heroesgetting younger and historical figures being brought back to life, but conceals the violence ofthe continuity solution staged by Robida in this counter-clockwise anticipation novel, as therestoration of order is achieved under the aegis of a mutilated Janus. This gave the momentumfor an anti-progressive eschatology, which turned out to have a great future in literature.